Maria Firmina dos Reis: Iyalodê do Brasil - Vrbata, Sidinea Almeida Pedreira (2018)
Historically, women have imposed themselves through the economic, political and social struggles. Thus, a writing tradition has been constituted and should be taken into consideration. During the nineteenth century, Literature starts being established in Brazil, as a possible space for these women expressions. Throughout published texts in periodicals, the women argue about daily life, landscapes, private world, and also, write the History; their networks are weaved, the country is imagined and told. Maria Firmina dos Reis, Maranhão citizen, socially stands out in reason of her performance as a black woman, teacher, abolitionist, composer and poet. This dissertation presents the author as Yalodê, Brazil’s interpreter, recognizing that her voice echoes in favour of women of her own time as well as contemporary women, representing them in their diversity. Her work is a biographic space in which black women and men feature and reinvent the Brazilian nation. The present study focuses on the novel Úrsula, the tale A Escrava, along with the author’s life and intellectual background. On the basis of concepts such as “escrevivência” by Conceição Evaristo, “Biographic space”, by Leonor Arfuch and “lugar de fala”, by Djamila Ribeiro, this work also emphasises Maria Firmina dos Reis’s pioneering spirit in black and afro-Brazilian writing, as well as black female authorship.